The impact of course evaluation on instructors' teaching performance - Abdul Karim, Abdul Malek; Abdullah, Syaharom (Universiti Utara Malaysia, 2007)
An investigation of the university course evaluation scores over four semesters was conducted to determine the impact of the University Teaching Evaluation practice on faculty teaching performance in general and (1) to measure how instructors perceive the effectiveness of the University Teaching Evaluation Programme, (2) to compare the course evaluation results based on gender, academic rank, and faculty, and (3) to determine additional measurement methods for evaluating teaching in particular.The results obtained lead us to conclude that most faculty members did not believe that course evaluation is valid and reliable. However, most of them indicated that the course evaluation practised in Universiti Utara Malaysia (UUM) has positive impact on them with regard to their awareness about their own teaching.Extraneous variables such as gender, academic rank, and faculty were significantly related to course evaluation mean scores.However, participation in the teaching certification programme was not a significant factor.Course evaluation, though believed to be lacking validity and reliability, was considered as good as some other more objective measures by the faculty members. There was also no evidence to suggest that improvement in course evaluation scores reflect better students’ learning. However, the questionnaire used may have captured not only some aspects of teaching effectiveness but also certain factors that are not related to teaching effectiveness.In conclusion, the course evaluation practice at UUM may not have produced better learning outcome as measured by students’ GPA, nevertheless, it has impacted positively on faculty members’ awareness about their own teaching performance.